The Effect Of Motivation And Anxiety On Students’ Speaking Performance: A Study At Dayanu Ikhsanuddin University - Sitti Nur Aisyah Ritonga; Nasmilah Nasmilah; Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study aims to know the effect of motivation and anxiety on students’ speaking performance: a study at Dayanu Ikhsanuddin University. The study was designed in the form of quantitative and qualitative descriptive studies (mixed methods). Subjects in this study were the 5th semester students of the teaching and education study program in Dayanu Ikhsanuddin University who took the speaking class as part of their courses. The data were collected by using the methods of observation, interviews, and questionairre. Data were analyzed through triangulation data. The results showed that language anxiety felt by students during their speaking presentation in English might result in their inability to deliver ideas clearly and this would have a negative impact on their performance. In contrast, langauge  motivation  during  speaking presentation would help students to feel less anxious and be more concentrated on the task and would result in a better speaking performance.